2020
DOI: 10.3762/bxiv.2020.90.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel 3-Acetoxy Fatty Acid Isoprenyl Esters from Androconia of the Ithomiine Butterfly Ithomia salapia

Abstract: Male ithomiine butterflies (Nymphalidae: Danainae) have hairpencils on the forewings (i.e. androconia) that disseminate semiochemicals during courtship. While most ithomiines are known to contain derivatives of pyrrolizidine alkaloids, dihydropyrrolizines or g-lactones in these androconia, here we report on a new class of fatty acid esters identified in two subspecies, Ithomia salapia aquinia and I. s. derasa. The major components were identified as isoprenyl (3-methyl-3-butenyl) (Z)-3-acetyloxy-11-octadecenoa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Chemical signals such as sex pheromones have been suggested to a play a role in reproductive isolation in mimetic butterflies (González-Rojas et al, 2020;Darragh et al, 2020), particularly among co-mimetic species (Mérot, Frérot, Leppik, & Joron, 2015). In ithomiine butterflies sexual pheromones have long been studied (Schulz et al, 2004), and have been shown to diverge between closely related taxa (Mann et al, 2020;McClure et al, 2019a;Stamm, Mann, McClure, Elias, & Schulz, 2019), suggesting a possible role in reproductive isolation (McClure et al, 2019b). More broadly, butterflies are phytophagous during the larval stage, and hostplant adaptation, mediated by chemical communication, has been hypothesized to be a major driver of speciation (Ehrlich & Raven, 1964;Jousselin & Elias, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical signals such as sex pheromones have been suggested to a play a role in reproductive isolation in mimetic butterflies (González-Rojas et al, 2020;Darragh et al, 2020), particularly among co-mimetic species (Mérot, Frérot, Leppik, & Joron, 2015). In ithomiine butterflies sexual pheromones have long been studied (Schulz et al, 2004), and have been shown to diverge between closely related taxa (Mann et al, 2020;McClure et al, 2019a;Stamm, Mann, McClure, Elias, & Schulz, 2019), suggesting a possible role in reproductive isolation (McClure et al, 2019b). More broadly, butterflies are phytophagous during the larval stage, and hostplant adaptation, mediated by chemical communication, has been hypothesized to be a major driver of speciation (Ehrlich & Raven, 1964;Jousselin & Elias, 2019).…”
Section: Introductionmentioning
confidence: 99%